Public Influences on Plantation Forestry - Glenn T. Howe; Bruce Shindler; Benjamin Cashore; Eric Hansen; Denise Lach; Ward Armstrong (Journal of Forestry, 2005)
For plantation forestry to be successful, it must be biologically possible, economically feasible, and culturally adoptable (i.e., socially acceptable). We discuss social acceptability and plantation forestry in the Pacific Northwest, stressing that social acceptability is a judgmental process that is both provisional and dependent on many complex factors, and that most decisions are based on intuition, rather than a rational evaluation of all relevant choices. We suggest that conflicts over plantation forestry can be minimized by carefully considering social acceptability and by forging formal agreements (accords) that promote the goals of both environmentalists and forest industries.